Yaşamsal krizlerde emzirme - Yeşim Aksoy Derya; Kader Atabey Kılıç (Journal of Infant, Child and Adolescent Health, 2026)
Aim: The aim of this review is to examine the effects of various life crises on the breastfeeding and lactation process, the challenges encountered, and the supportive approaches that can be implemented in such situations, in light of the existing literature. Method: As part of this review, publications concerning life crises and breastfeeding were examined across the PubMed, Scopus, Web of Science, and Google Scholar databases. The findings from the literature were synthesized under nine thematic areas: sexual abuse, domestic violence, institutional care, divorce and single parenthood, incarceration, cancer and surgical interventions, vegetative state, infant loss, and adoption. Results: It has been observed that life crises can influence the initiation and continuation of breastfeeding through physical, psychological, social, and institutional mechanisms. While sexual abuse and domestic violence can trigger traumatic experiences during breastfeeding, appropriate support can contribute to the continuation of breastfeeding for some women. Social, logistical, and institutional barriers are prominent in situations involving institutional care, single parenthood, and incarceration. In cases of cancer and surgical interventions, the decision regarding breastfeeding must be evaluated based on the administered treatment and the mother's clinical status. While lactation management in cases of persistent vegetative state and infant loss involves unique issues encompassing clinical, ethical, and individual preferences, induced lactation emerges as an option for initiating breastfeeding in adoption scenarios. Conclusion: In life-threatening crises, breastfeeding and lactation management should be individualized according to the safety of the mother and baby, clinical needs, and the mother's preferences. It is important for healthcare professionals to provide evidence-based, trauma-sensitive, non-judgmental, and multidisciplinary care.